2014
DOI: 10.1002/2013wr014194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognostic and diagnostic surface flux modeling approaches over the Nile River basin

Abstract: [1] Regional evapotranspiration (ET) can be estimated using diagnostic remote sensing models, generally based on principles of energy balance closure, or with spatially distributed prognostic models that simultaneously balance both energy and water budgets over landscapes using predictive equations for land surface temperature and moisture states. Each modeling approach has complementary advantages and disadvantages, and in combination they can be used to obtain more accurate ET estimates over a variety of lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 97 publications
4
67
0
Order By: Relevance
“…CLSMF2.5 agrees well with ALEXI during both high and low periods, whereas Noah3.3 has decreased ET values, close to GLEAM values during those low periods. Yilmaz et al (2014) also demonstrated that Noah3.2 captures ET well during the rainy season, but it underestimated ET during the winter months over agricultural areas or regions with shallow ground water tables in the Nile Basin. In this sense, the Noah-MP LSM (Niu et al, 2011) may better represent ET values in this region due to being coupled with an underlying water table scheme, which is not supported in Noah3.3.…”
Section: Evaluation Of Model Evapotranspiration Estimatesmentioning
confidence: 87%
See 3 more Smart Citations
“…CLSMF2.5 agrees well with ALEXI during both high and low periods, whereas Noah3.3 has decreased ET values, close to GLEAM values during those low periods. Yilmaz et al (2014) also demonstrated that Noah3.2 captures ET well during the rainy season, but it underestimated ET during the winter months over agricultural areas or regions with shallow ground water tables in the Nile Basin. In this sense, the Noah-MP LSM (Niu et al, 2011) may better represent ET values in this region due to being coupled with an underlying water table scheme, which is not supported in Noah3.3.…”
Section: Evaluation Of Model Evapotranspiration Estimatesmentioning
confidence: 87%
“…Significant uncertainty in evapotranspiration analyses has been a known issue in the region (Yilmaz et al, 2014). In this study, we evaluated the 16 modeled ET estimates against ALEXI data, which have also been used to validate actual ET estimates in this region (Allam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These significant potential impacts of irrigation on temperature, clouds, precipitation, and related fluxes necessitate an appropriate representation of irrigation in coupled landatmosphere models. This need has been addressed via irrigation parameterizations in LSMs that largely fall into three types of schemes: (1) defined increases to soil moisture in one or more soil layers (Kueppers and Snyder, 2011;de Vrese et al, 2016), sometimes referred to as flood (Evans and Zaitchik, 2008); (2) the addition of water as pseudoprecipitation to mimic sprinkler systems (Ozdogan et al, 2010;Yilmaz et al, 2014); and (3) modifications to vapor fluxes as a proxy for increased evapotranspiration resulting from highly efficient (e.g., drip) irrigation (Douglas et al, 2006;Evans and Zaitchik, 2008). These schemes are generally dependent on parameter input datasets and user-defined thresholds, affording a degree of customization, but also introducing uncertainty and potential error.…”
Section: Irrigation Physicsmentioning
confidence: 99%